Revisioning the Shawnee Prophet: Revitalization Movements, Religious Studies, and the Ontological Turn. - Winiarski, Douglas (Early American Studies, An Interdisciplinary Journal)
Historians invariably frame the early life of Laloeshiga, more commonly known as Tenskwatawa, the Shawnee Prophet, as one of unmitigated chaos and disorder. He emerges in scholarly literature as a ne'er-do-well: failed hunter and warrior, adulterer and wife beater, penurious healer, and dissolute alcoholic. A near-death experience during the winter of 1805 triggered visions that led to his rapid rise to religious authority in the revitalization movement he led with his brother, the famed Shawnee leader Tecumseh. Newly discovered sources and systematic review of older ones reveal a vastly different origin story. None of the supposed facts of the Prophet's early life, character, or visions can be substantiated by the documentary record. Scholars have worked for decades in the shadow of dubious nineteenth-century biographies and twentieth-century social theories that translate charismatic religion into narratives of medical pathology or social stress. Cutting through the tangle of myth and misinformation obscuring the Shawnee Prophet's origins, the following argument attempts to clear a path toward a new understanding of Tenskwatawa's prophetic career grounded in recent theories of religion as presence.